Measuring housing costs and housing affordability using SOEP: An example applied to older households - Alberto Lozano Alcántara; Laura Romeu Gordo (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
This paper explores the methodological issues to take into account when using SOEP as a database for calculating a measure of housing costs and housing affordability. For this purpose, we focus on the evolution of housing costs for households headed by elderly people between 1998 and 2018. Our review yields two clear conclusions: (1) that SOEP represents a valuable source of data for calculating household housing costs; and (2) that it is important to take changes made in the SOEP questionnaires into account and to make the appropriate assumptions when one wishes to analyse how housing costs have evolved over time (or how they evolve over the life course). Besides, our results confirm previous studies (Romeu Gordo, Grabka, Lozano Alcántara, Engstler, & Vogel, 2019) by showing that housing costs tend to be higher for elderly tenants than for the homeowners and that this difference widened during the period between 1998 and 2018.
Keywords: 330; Wohnkosten; Ältere Menschen; Soziale Lage; Panel; Deutschland